Single Mothers and Their Children: Evaluating a Work-Encouraging Welfare Reform - Katrine Vellesen Løken; Kjell Erik Lommerud; Katrine Holm Reiso (Institute for the Study of Labor (IZA), 2016)
Using rich administrative data from Norway, we evaluate a 1998 work-encouraging reform targeted at single parents. We especially focus on educational performance for children of the involved single mothers. For all children of single mothers, the effect on school grades at completion of junior high school at age 16 is near zero and insignificant. If one concentrates on younger single mothers, those most likely to be affected by the reform, the grade point average of their children drops significantly by 7% of a standard deviation. We isolate groups of mothers who are affected by the reform either primarily by having less time at home, or by reduced income. The children of both groups of mothers experience drops in school grades, so both reduced parental time and reduced income matter. The effect of reduced parental time, though, seems to be the more important.
Keywords: I24; I38; J13; 330; welfare reform; single mothers; child development; time and money investments